Estresses abióticos em plantas transformadas e não transformadas de tomate Micro-Tom com diferentes expressões da sHSP22 mitocondrial: Efeito do alagamento e de ciclos de alta e baixa temperatura. - Hüther, Cristina Moll (2011)
The abiotic stress often cause metabolic disorders which cause a decrease in plant growth. In response to stress, an increase in the synthesis of certain proteins called ―heat shock proteins‖ (HSPs), might occur. The tomato (Lycopersicon esculentum) cv. Micro-Tom is regarded as a model for experimental studies, and that is because it has features that make it appropriate, such as small size, short development time and easy modification. This study aimed to evaluate the stress effects by flooding and by high and low temperatures in both modified and not modified ‗Micro-Tom tomato plants which have different mitochondrial expressions (MT- sHSP22). The first experiment was conducted in growth chambers under controlled conditions. When the plants were 50 days, they were submitted to stress by flooding during 14 days, and after 7 days, half the plants were removed from the flooding. In the second trial, plants were grown as in the first experiment, and when they presented themselves in a complete vegetative stage, they were submitted to thermal stress for a period of 24 hours of 10 ºC or 37 °C, soon after that, the plants were transferred to the initial conditions for 24 hours. After this phase they were again subjected to a new cycle of stress and recovery. On both experiments were evaluated parameters of the kinetic emission of chlorophyll fluorescence and of gas exchange, taking into account that in the first was also evaluated the content of chlorophyll, and, at the end of the test, the leaf area and the dry mass of the upper area and root. The flooding interfered on the the chlorophyll content of all genotypes, and on the genotype with a high expression of MT-sHSP22, a decrease in the leaf area was not identified and neither was in the total dry mass. The kinetics analysis of the transient fluorescence of chlorophyll showed differential effects of stress by flooding in the different parts of the photosynthetic machinery, and showed different responses between genotypes. When plants were submitted to stress by low temperature, a reduction in the liquid CO2 rate was noticed immediately after the stress, but, after recovery, all genotypes returned close to the controls. For plants submitted to high temperatures of the wild genotype and with high expression of MT-sHSP22 increased the liquid assimilation rate in comparison to control. The chlorophyll fluorescence data indicated different effects on absorption and utilization of light energy between the two genotypes for two of the temperature stress. The interpretation of the JIP test parameters helped to identify that three genotypes exhibit different behavior, mainly on high-temperature stress, and the plants of high expression genotypes of HSP22 and not transformed showed an increase in the parameters related to the photosystem I activity. These results suggest that plants with high doses of mitochondrial sHSP22 may present mechanisms of tolerance against the applied stress.